O porto de Viana e a construção do Cais da Alfândega (1631-1633) - Barros, Amândio Jorge Morais (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
During the Early Modern Period the maritime traffic became a decisive factor for the prosperity of the societies. As noted by James D. Tracy in the introduction to an important book on the organisation of the world’s economy (The political economy of merchant empires), it was necessary to deal “with important changes in the growth and composition of the long distance commerce grosso modo between 1450 and 1750” which resulted in the primacy of Europe in the global trade. Researchers consider that this was due, essentially, to evolved organisational processes. While concerned about the protection of their navies and strategic routes, states, political powers and private entities began to give special attention to port logistics: the ports were modernised with quays, warehouses and service areas. In this article, I will address some aspects relating to the evolution of Viana do Castelo harbour in the first half of the 17th century. Constituted as one of the strategic ports of the Portuguese Atlantic trade, and open to international navigation, this anchoring-place was object of profound improvements which culminated in the construction of a quay: the “Custom House Quay”, a work whose technical steps we can follow thanks to a precious income and expense document concerning this undertaking, conserved in a particular archive.